Oral Health Literacy Rate Among Schoolteachers—A Quantitative Study - Ain, Qurat-ul; Gillani, Syeda Munazza; Ain, Qurat-ul (European Dental Research and Biomaterials Journal, 2023)
Objective The aim of this study was to evaluate oral health literacy (OHL) rate among schoolteachers of Abbottabad city by using structured questionnaire divided in sections of reading skills, numeracy, listening skills, and appropriate decision-making skills.Materials and Methods Descriptive cross-sectional study was conducted among schoolteachers with survey method. Total 159 participants were selected as sample from 10 different local schools of Abbottabad city. Data was gathered by using OHL-AQ (oral health literacy-adult questionnaire) with convenient sampling technique. Responses were calculated by using IBM SPSS.V.26 and descriptive analyses were performed.Results Satisfactory results were seen among schoolteachers: high-level of OHL, 44.65%; moderate level of OHL, 40.9 and low-level OHL, 14.46%. The questionnaire section, “numeracy-calculation skills” and “appropriate decision-making skills,” exhibited high scores.Conclusion This study concluded that the OHL rate among schoolteachers was satisfactory. But as teachers play a pivotal role in shaping and influencing young minds, setting a goal of achieving 100% would ensure commitment toward better oral health of their wards. Those participants who showed considerably low OHL level is alarming for oral health challenges.
Keywords: school teacher; OHL level; score; OHL-AQ